Utilization of antagonistic bacteria and fungi for inducing resistance in red chili and cayenne pepper in Tanjung Dayang Utara - Weri Herlin; Siti Herlinda; Yulia Pujiastuti; Rizki Palupi; Oktaviani Oktaviani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Plant health problems caused by pests and diseases remain a significant challenge for farmers, especially in cultivating red curly chili and cayenne pepper. Conventional reliance on synthetic pesticides raises environmental and economic concerns. This community service program aimed to enhance farmers' knowledge in using biological agents as alternatives to synthetic pesticides to strengthen plant resistance. The program was carried out in Tanjung Dayang Utara Village, Ogan Ilir, through stages of preparation, implementation, evaluation, mentoring, and monitoring. Methods included lectures and demonstrations on using Pseudomonas fluorescens and Trichoderma sp. through seed soaking and soil or foliar application. A total of 50 farmers attended, receiving both theoretical and practical training. The evaluation was conducted in three phases: pre-, during, and post-activity. Previous approaches relied heavily on synthetic pesticides, while recent innovations emphasize ecological pest management using microbial antagonists. The outcomes showed a high level of enthusiasm and improved understanding among farmers regarding natural pest resistance mechanisms. Farmers were able to practice the propagation and application of beneficial microbes supported by educational materials. The program reduced farmers' dependency on chemical inputs and contributed to sustainable agricultural practices. This model using replicable in similar agroecosystems facing pest and disease issues. The main problem addressed was farmers’ limited knowledge and skills in utilizing biological control agents as environmentally friendly alternatives. The implementation consisted of preparation, training through lectures and demonstrations, field practice, and evaluation. The results indicated measurable improvements, including increased knowledge based on evaluation scores and reduced reliance on chemical pesticides